2011
DOI: 10.3109/09546634.2011.579084
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of localized non-segmental vitiligo with intradermal 5-flurouracil injection combined with narrow-band ultraviolet B: A preliminary study

Abstract: Intradermal 5-FU injection in combination with NB-UVB could be considered as a simple, safe, tolerable and cheap technique for treatment of vitiligo. It shortens the duration of NB-UVB therapy and improves the outcome, repigmentation. Longer follow-up is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 17 publications
7
27
3
Order By: Relevance
“…However, the acral parts showed poor response and hardly repigmented and statistically not significant than the control group, and this coincides with the previous studies . The acral parts and areas over bony prominence were difficult to repigment because few hair follicle density, which are the reservoir of melanocytes and also thick skin.…”
Section: Discussionsupporting
confidence: 87%
“…However, the acral parts showed poor response and hardly repigmented and statistically not significant than the control group, and this coincides with the previous studies . The acral parts and areas over bony prominence were difficult to repigment because few hair follicle density, which are the reservoir of melanocytes and also thick skin.…”
Section: Discussionsupporting
confidence: 87%
“…Although 5‐fluorouracil was applied topically after microneedling in this study, its efficacy was close to the results of its intradermal injection combined with NBUVB which had been studied by Abd El samad et al, who reported that 48.3% of the treated patches showed marked response (repigmentation >50%), while in this study, 52% showed marked response with 5‐fluorouracil and microneedling. This means that microneedling can be used as alternative procedure to introduce the drug into the dermis instead of direct intradermal injection.…”
Section: Discussionsupporting
confidence: 84%
“…This means that microneedling can be used as alternative procedure to introduce the drug into the dermis instead of direct intradermal injection. In addition, the cosmetic outcome of microneedling combined with 5‐fluorouracil was better than intradermal injection which showed hyperpigmentation at the periphery of the treated lesions and pigment incontinence in 25% of the patients …”
Section: Discussionmentioning
confidence: 99%
“…Depigmentation arises from the loss of functioning melanocytes38. Treatment is often a tough challenge and involves a wide range of therapies39 including UV radiation, laser40-42, transplant43, 44, and complementary medicine45-47. The most efficient therapy remains autologous skin graft, performed successfully daily in some of the dermatology clinics.…”
Section: Discussionmentioning
confidence: 99%